Critical Factors for the Development of a Smart, Sustainable and Resilience Mobility Ecosystem in a Circular Economy - Urszula MOTOWIDLAK; Agnieszka BUKOWSKA-PIESTRZYŃSKA (Communications of International Proceedings, 2021)
The aim of the article is to indicate technological, organizational and social solutions that have a high potential in shaping the model of „green” mobility in the networked Smart ecosystem, in accordance with the assumptions of the circular economy. Selected critical factors shaping the development of the new mobility ecosystem were analyzed. The study developed a smart, sustainable and resilience model for a mobility ecosystem in the circular economy, consistent with the universal set of ReSOLVE activities. To achieve the assumed goal, the method of analysis of the literature on the subject, the method of logical inference analysis, the analysis of the results of the author's research, the analysis of theoretical and practical aspects in relation to the critical factors of the development of intelligent, „green” mobility were used. The results of the carried out analyzes indicate that innovations and business models in mobility systems are fundamentally changing thanks to the new generation of consumers who expect value co-creation. Business models that shift from ownership to use will play an important role in disseminating the circular concept to the mobility ecosystem. The article justifies the sense of conducting research on the impact of technological innovations, social and organizational changes in shaping the new mobility paradigm 3.0, in accordance with the concept of sustainable economy. Practical conclusions may be used in the process of implementing the concept of an intelligent, sustainable and resilience model of the mobility ecosystem, in accordance with the assumptions of the circular economy.
Keywords: Intelligent and sustainable mobility ecosystem; circular economy; new mobility services; changes in social behavior